Historical, technological and medial a priori: on the belatedness of media. - Tuschling, Anna (Cultural Studies, 2016)
This essay addresses German-language media theory through the lens of its central concept, the technological a priori. The technological a priori is a concept developed most prominently in the work of Friedrich Kittler out of the historical a priori of Michel Foucault’s discourse analysis. The focus of the technological a priori is historically significant materialities, that is, media technologies. This essay argues that the technological a priori precisely cannot be reduced to analysing specific materialities, such as individual media technologies, the computer, gramophone, telephone, etc. in terms of their fundamental significance for sense-making and history. The technological a priori entails not only a concept of materiality but also a concept of time. The media studies to come should expand the technological a priori towards a more general media a priori by incorporating more complex theories of time such as those offered by various approaches to belatedness. This task would prove especially compelling for the history of media and the disciplinary history of media studies.